Determination of S alleles in Iranian sour cherry (Prunus cerasus) using consensus primers - aliyoun nazari, samad (Journal of Agricultural Sciences (Belgrade), 2024)
Sour cherry is a tetraploid species, and gametophytic self-incompatibility (SI) operates in this species as well as in other stone fruit trees. However, while in sweet cherry SI is most common and self-compatibility (SC) genotypes are rarely found, in sour cherry both SC and SI selections are found. In this work, S-alleles have been identified for 70 sour cherry accessions and cultivars from Shabestar regions of Iran, with S-genotypes of 68 cultivars identified for the first time. To identify the S-alleles, PCR-based methods were used. The amplification of the different alleles using combinations of the four forward (PaConsI-F, PruC2, PaConsII-F, EM-PC2consFD) and the five reverse primers (PruC4R, PCE-R, PaConsI-Rnew, PaConsII-R, EM-PC5consRD) revealed that the most useful for the identification of sour cherry alleles. Nine known S-haplotypes (S6, S4, S9, S6m, S6m2, S24, S26, S35, S36a) were identified. In our study alleles S6, S9, S6m2 have a high frequency. The potential use of the consensus primers to reveal incompatibility alleles in sour cherry accessions is demonstrated.